Formation of three-dimensional image of the medium by the sum of CDP for the studies of geological structure of mine fields - Pilipenko, V.; Verpahovskaya, A.; Budkevich, V.; Pilipenko, E. (S. Subbotin Institute of Geophysics of the NAS of Ukraine, 2015)
Traditionally, seismic observations are carried out by the reflected wave method with multiple overlaps. Thus, the primary result of the processing of such data is the sum of CDP. For further imaging there is necessary to have the correct variant of migration without restrictions on the angle of reflectors, which is particularly important for the study of the geological structure of the mine fields.The paper presents a three-dimensional variant of the full-wave finite-difference migration in the time scale of the depths. That variant allows defining delicate structural features of the environment, the velocity model of which can be non-uniform across the board. The effectiveness of the proposed method to study the geological structure of the mine fields is demonstrated on a model example and practical materials observed in the Donbas region.